Zirconium in the Nuclear Industry 1987
DOI: 10.1520/stp28156s
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Fracture Properties of Neutron-Irradiated Recrystallized Zircaloy-2 Cladding under Uniaxial Tension

Abstract: Sufficient evaluation of the changes in mechanical properties, such as elastic, plastic, and failure properties, due to neutron irradiation in service is required to precisely predict fuel performance. This paper presents the results of the uniaxial tensile tests performed for recrystallized (850 K, 2.5 h) Zircaloy-2 claddings irradiated in commercial BWRs to fluences of 5 × 1023 to 4 × 1025 n/m2 (E > 1 MeV). The material constants of irradiated Zircaloy-2 were obtained precisely, using a high temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…This result is larger than the 570-MPa yield strength reported for the as-received material in the annealed condition and is greater than most values reported in the literature for unirradiated Zircaloy-4. [5][6][7][8][15][16][17] However, it is worth noting that in a study using burst tests, Yagnik et al 18 reported hoop strength similar to those measured here for room temperature tests of unirradiated Zircaloy-4. A more detailed analysis of cladding deformation will be addressed in future efforts.…”
Section: Estimates Of Stress and Strainsupporting
confidence: 75%
See 4 more Smart Citations
“…This result is larger than the 570-MPa yield strength reported for the as-received material in the annealed condition and is greater than most values reported in the literature for unirradiated Zircaloy-4. [5][6][7][8][15][16][17] However, it is worth noting that in a study using burst tests, Yagnik et al 18 reported hoop strength similar to those measured here for room temperature tests of unirradiated Zircaloy-4. A more detailed analysis of cladding deformation will be addressed in future efforts.…”
Section: Estimates Of Stress and Strainsupporting
confidence: 75%
“…The angled fracture surface is consistent with previously reported results for room temperature testing of irradiated Zircaloy. 6 The high-magnification image (upper left of Fig. 46) reveals a dimpled fracture surface typical of ductile fracture.…”
Section: Fracturementioning
confidence: 99%
See 3 more Smart Citations